2010
DOI: 10.4049/jimmunol.1001912
|View full text |Cite
|
Sign up to set email alerts
|

CD8 T Cell-Intrinsic GITR Is Required for T Cell Clonal Expansion and Mouse Survival following Severe Influenza Infection

Abstract: Material Supplementary 2.DC1http://www.jimmunol.org/content/suppl/2010/11/12/jimmunol.100191References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
115
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(127 citation statements)
references
References 50 publications
10
115
0
Order By: Relevance
“…Here we show that TRAF1, as well as cIAP1 or 2, are required for 4-1BB induced canonical NF-B activation. It is unlikely that the defect in canonical NF-B signaling in TRAF1 Ϫ/Ϫ T cells is due to a generalized defect in TRAF1 Ϫ/Ϫ T cells, as we previously showed that TRAF1 is dispensable for activation of the canonical NF-B pathway downstream of another TNFR member, GITR (6). In the case of GITR, we found instead that TRAF2 and TRAF5 cooperated in canonical NF-B signaling (6), perhaps explaining why TRAF1 was not needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we show that TRAF1, as well as cIAP1 or 2, are required for 4-1BB induced canonical NF-B activation. It is unlikely that the defect in canonical NF-B signaling in TRAF1 Ϫ/Ϫ T cells is due to a generalized defect in TRAF1 Ϫ/Ϫ T cells, as we previously showed that TRAF1 is dispensable for activation of the canonical NF-B pathway downstream of another TNFR member, GITR (6). In the case of GITR, we found instead that TRAF2 and TRAF5 cooperated in canonical NF-B signaling (6), perhaps explaining why TRAF1 was not needed.…”
Section: Discussionmentioning
confidence: 99%
“…Although CD28 provides the primary costimulatory signal, the sustained survival of T cells requires that they receive additional signals through tumor necrosis factor receptor (TNFR) 3 family members (2,3). For example, the TNFR family members 4-1BB, CD27, and glucocorticoid-inducible TNFR-related (GITR) have all been shown to play important roles in sustaining the survival of CD8 T cells following their initial antigen and CD28-dependent activation (3)(4)(5)(6)(7)(8). This sequential regulation of T cell survival by different costimulatory receptors is thought to provide precise regulation of the duration of the T cell response to allow an appropriate response to pathogens, while preventing immune pathology (9).…”
mentioning
confidence: 99%
“…Traf5 −/− CD4 + T cells have impaired GITR cosignaling and defective GITR-mediated canonical NF-κB, p38, and ERK activation (Esparza et al 2006). The GITR-mediated canonical NF-κB is diminished in small interfering RNA-mediated TRAF5-knockdown CD8 + T cells (Snell et al 2010). Although the proliferation and survival mediated by CD27 cosignaling are impaired in Traf5 −/− T cells, the CD27-mediated activation of canonical NF-κB and MAPKs is not altered, suggesting functional redundancy between TRAF2 and TRAF5 in CD27 cosignaling (Nakano et al 1999;Kraus et al 2008).…”
Section: Traf5 In Signalmentioning
confidence: 80%
“…The GITR-induced canonical NF-κB, which upregulates Bcl-x L , is impaired in small interfering RNA-mediated TRAF2-knockdown CD8 + T cells (Snell et al 2010).…”
Section: Traf2 In Signalmentioning
confidence: 99%
See 1 more Smart Citation